2014
DOI: 10.1380/ejssnt.2014.141
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Light-Emitting Electrochemical Cells (LECs) from Host-Guest Cationic Iridium(III) Complexes

Abstract: Five charged iridium(III) complexes with a different number and position of methyl group; [Ir(phen)(ppy)2]PF6 (1), [Ir(4-phen)(ppy)2]PF6 (2), [Ir(2,9-phen)(ppy)2]PF6 (3), [Ir(4,7-phen)(ppy)2]PF6 (4) and [Ir(4,5,6,7-phen)(ppy)2]PF6 (5) were synthesized and characterized by NMR, IR, UV-Vis absorption, fluorescence spectroscopy and cyclic voltammetry. The host-guest light-emitting electrochemical cells (LECs) based on ITO/PEDOT:PSS/1-5:PVK (1:4)/Al were investigated, which resulted in a maximum current efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The calculated energy gap of UM02 shows a value at 3.37 eV which is in agreement with the result from photophysical experiments (3.10 eV). In order to evaluate the electroluminescent properties, complexes were rst employed as emitting layer in both host-guest LECs [15] and OLEDs [16,17] where PVK and PBD were mixed as the co-host. PEDOT:PSS acts as hole-injecting layer to facilitate electron transport.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated energy gap of UM02 shows a value at 3.37 eV which is in agreement with the result from photophysical experiments (3.10 eV). In order to evaluate the electroluminescent properties, complexes were rst employed as emitting layer in both host-guest LECs [15] and OLEDs [16,17] where PVK and PBD were mixed as the co-host. PEDOT:PSS acts as hole-injecting layer to facilitate electron transport.…”
Section: Resultsmentioning
confidence: 99%
“…Heteroleptic charged iridium (III) species comprising two cyclometallating ligands and a neutral diimine ligand of generic formula (C ∧ N) 2 Ir(N ∧ N) + have been of great interest as multifunctional chromophores for advanced optoelectronic applications [16]. The key properties of these complexes are their high stabilities, high luminescence quantum yields, short excited state lifetime and tunable emission energies.…”
Section: Introductionmentioning
confidence: 99%
“…4 and summarized in Table 2. The OLED performances suggested that bis(4-alkoxyphenyl) substituted 4,5-diazafluorene derivatives gave a beneficial N^N ligand, compared with 3,4,6,7-tetramethyl-1,10-phenanthroline in previous work [15]. Moreover, the long alkyl chains (C6 and C8) showed the better OLEDs performances than C1.…”
Section: Fig 3 Configuration and Energy Profile (Ev) Of Oleds Devicesmentioning
confidence: 78%